The Ukrainian night : an intimate history of revolution - Shore, Marci (New Haven : Yale University Press, 2017)
What is worth dying for? While the world watched the uprising on the Maidan as an episode in geopolitics, those in Ukraine during the extraordinary winter of 2013-14 lived the revolution as an existential transformation: The blurring of night and day, the loss of a sense of time, the sudden disappearance of fear, the imperative to make choices. In this lyrical book, Marci Shore evokes the human face of the Ukrainian Revolution. Grounded in the true stories of activists and soldiers, parents and children, Shore's book blends a narrative of suspenseful choices with a historian's reflections on what revolution is and what it means. She gently sets her portraits of individual revolutionaries against the past as they understand it - and the future as they hope to make it. In so doing, she provides a lesson about human solidarity in a world, our world, where the boundary between reality and fiction is ever more effaced. - from bookjacket.
Machine generated contents note: pt. 1 Revolution, the Maidan -- Sky Turns Black from Smoke -- Land of Gogol -- Grandeur of Its Intentions -- Fantasies of Galicia -- Revolutions That Were Not -- "Likes" Don't Count -- Fathers and Sons -- Self-Organization -- Bell Tower -- Noah's Ark -- "It was my choice" -- When Time Was Smashed -- Automaidan -- Values -- Very Atmosphere Had Some Qualities -- Nonanalytical Point -- Buses from Lviv -- Corpses -- Solidarity of the Shaken -- Burning Flesh -- "You will all be dead" -- Pornographic Portraits -- Revolutionary Soul -- Dialectics of Transparency -- Chekhov's Gun -- pt. 2 War, East of Kiev -- Russian Tourists -- Caligula at the Gates -- Grandma at War -- Nothing Is True (The Surrealism of Ostriches) -- Putin's Sirens -- Zhidobandera on the Dnipro -- Smart Kids Like You -- "We understood perfectly ..." -- Volunteer Movement -- Specter of Communism -- Civilizational Choice -- Black Lizard on Red Square -- Free Hugs for Patriots -- Divided Families -- Alchevsk -- Zombies in the Donbas -- Time Is Out of Joint -- World Order -- Goodbye, Lenin -- Cicero's Rome -- Do We Know the Ukrainian Night? -- "We cannot be bought" -- Theater of the Absurd -- Dostoevsky's Demons -- "At the end of the day this soldier feels sorry" -- Ice Skating Lessons -- There Is No Absolute -- Everything Is Possible -- Dictionary of Translatable and Untranslatable Words.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Ukraine -- History -- Revolution of Dignity, 2013-2014 -- Personal narratives; Russo-Ukrainian War, 2014-; Russo-Ukrainian War, 2014- -- Personal narratives; Ukraine -- Politics and government -- 1991-2014.; Ukraine -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- Ukraine; Electronic books; Guerre russo-ukrainienne, 2014-; Guerre russo-ukrainienne, 2014- -- Récits personnels; Ukraine -- Politique et gouvernement -- 1991-2014.; Ukraine -- Relations extérieures -- Russie; Livres numériques.; e-books.; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; HISTORY / Russia & the Former Soviet Union; Diplomatic relations; Politics and government; Russia (Federation); Ukraine; Since 1991; Downloadable e-Books; Personal Narrative; Personal narratives; Personal narratives; Récits personnels